1995
DOI: 10.1177/08959374950090011001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Actinobacillus Actinomycetemcomitans Invasion of and Adhesion to Cultured Epithelial Cells

Abstract: Two quantitative, rapid assays were developed to study the adhesion ofActinobacillus actinomycetemcomitans, an oral bacterium associated with periodontal disease, to human epithelial cells. The human oral carcinoma cell line KB was grown in microtiter plates, and adherent bacteria were detected by an enzyme-linked immunosorbent assay with purified anti-A. actinomycetemcomitans serum and horseradish peroxidase-conjugated secondary antibody or [3H]thymidine-labeled bacteria. Adhesion was found to be time depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 42 publications
2
62
0
4
Order By: Relevance
“…These effects of biofilms may induce persistent infection in periodontal lesions. It has been suggested that periodontal disease-associated bacteria can penetrate gingival tissues and enter the bloodstream (8,19). Microorganisms in the periodontal pocket may also induce a continuous benign bacteremia (5,22,32).…”
mentioning
confidence: 99%
“…These effects of biofilms may induce persistent infection in periodontal lesions. It has been suggested that periodontal disease-associated bacteria can penetrate gingival tissues and enter the bloodstream (8,19). Microorganisms in the periodontal pocket may also induce a continuous benign bacteremia (5,22,32).…”
mentioning
confidence: 99%
“…actinomycetemcomitans, a gram-negative, facultative anaerobic bacterium, is widely distributed across human populations and is strongly associated with periodontal diseases (10,33). This bacterium is found associated with or internalized in buccal and gingival epithelial cells, as well as connective tissue in the oral cavity (7,23,31). Colonization of the connective tissue may allow this opportunistic pathogen to cause other serious systemic infections, including endocarditis, pulmonary infections, and osteitis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Gingival keratinocytes contribute to periodontal disease progression by the secretion of several pro-inflammatory cytokines, including IL-1, IL-6, and IL-8, and the expression of adhesion molecules, which aid in the influx of leukocytes into the gingival sulcus. Epithelial tissues act as physical barriers to the outside environment; however, unlike normal plaque flora, the periodontopathogens P. gingivalisand A. actinomycetemcomitanscan disrupt the gingival epithelial barrier by adhering to and invading epithelial cells and even the connective tissues in diseased sites (Sandros et al ., 1993;Fives-Taylor et al , 1995), highlighting the possibility of antigen presentation of P. gingivalis and A. actinomycetemcomitans antigens by gingival keratinocytes (Saglie et al ., 1988). Keratinocytes function as accessory cells by activating T-cells via the TCR/CD3 complex, and this involves signals by the adhesion molecules ICAM-1 (CD54) on the keratinocyte and LFA-1 (CD11a) on the T-cell (Nickoloff et al ., 1993).…”
Section: (V) Animal Modelsmentioning
confidence: 99%